E-selectin in vascular pathophysiology - Zhang, Jinjin; Huang, Shengshi; Zhu, Zhiying; Gatt, Alex; Liu, Ju (Frontiers in Immunology, 2024)
Selectins are a group of Ca 2+ -dependent, transmembrane type I glycoproteins which attract cell adhesion and migration. E-selectin is exclusively expressed in endothelial cells, and its expression is strongly enhanced upon activation by pro-inflammatory cytokines. The interaction of E-selectin with its ligands on circulating leukocytes captures and slows them down, further facilitating integrin activation, firm adhesion to endothelial cells and transmigration to tissues. Oxidative stress induces endothelial cell injury, leading to aberrant expression of E-selectin. In addition, the elevated level of E-selectin is positively related to high risk of inflammation. Dysregulation of E-selectin has been found in several pathological conditions including acute kidney injury (AKI), pulmonary diseases, hepatic pathology, Venous thromboembolism (VTE). Deletion of the E-selectin gene in mice somewhat ameliorates these complications.